NextGen protein design - Sawyer, Nicholas (2013)
Protein engineering is at an exciting stage because designed protein–protein interactions are being used in many applications. For instance, three designed proteins are now in clinical trials. Although there have been many successes over the last decade, protein engineering still faces numerous challenges. Often, designs do not work as anticipated and they still require substantial redesign. The present review focuses on the successes, the challenges and the limitations of rational protein design today.